The Common European Framework of Reference (CEFR) in Canada: A Research Agenda - Arnott, Stephanie; Brogden, Lace Marie; Faez, Farahnaz; Péguret, Muriel; Piccardo, Enrica; Rehner, Katherine; Taylor, Shelley K.; Wernicke, Meike (Canadian Journal of Applied Linguistics, 2017)
Abstract This article proposes a research agenda for future inquiry into the use of the Common European Framework of Reference (CEFR) in the plurilingual Canadian context. Drawing on data collected from a research forum hosted by the Canadian Association of Second Language Teachers in 2014, as well as a detailed analysis of Canadian empirical studies and practice-based projects to date, the authors examine three areas of emphasis related to CEFR use: (a) K-12 education, including uses with learners; (b) initial teacher education, where additional language teacher candidates are situated as both learners and future teachers; and (c) postsecondary language learning contexts. Future research directions are proposed in consideration of how policymaking, language teaching and language learning are articulated across each of these three contexts. To conclude, a call is made for ongoing conversations encouraging stakeholders to consider how they might take up pan-Canadian interests when introducing various aspects of the CEFR and its related tools. Résumé Cet article propose un programme de recherche en vue d’études futures sur l’utilisation du Cadre européen commun de référence (CECR) dans le contexte plurilingue canadien. S’appuyant sur des données recueillies lors d’un forum de recherche organisé par l’Association canadienne des professeurs de langues secondes en 2014, ainsi que sur une analyse détaillée d’études empiriques et basées sur la pratique canadiennes actuelles, les auteurs ont examiné trois domaines d’intérêt liés à l’utilisation du CECR : (a) l’éducation de la maternelle à la douzième année, y compris les utilisations du CECR avec les apprenants ; (b) la formation initiale à l’enseignement, où les candidats à l’enseignement d’une langue additionnelle sont à la fois des apprenants et de futurs enseignants ; et (c) les contextes d’apprentissage des langues au niveau postsecondaire. Des axes de recherche future sont proposés qui tiennent compte de la façon dont l’élaboration des politiques, l’enseignement des langues et l’apprentissage des langues sont articulés dans chacun des trois contextes. Pour conclure, un appel est lancé pour encourager l’échange entre acteurs intéressés dans l’espoir d’une prise en compte des intérêts pancanadiens lors de la mise en œuvre du CECR et des outils connexes.